The Impact of New Legal Regulations on The Functioning of Businesses Based on The Example of Atomic Law in Poland - Maja JOKIEL; Grzegorz JOKIEL; Robert BOBKIER; Arkadiusz BABCZUK (Communications of International Proceedings, 2023)
The motive behind the study is the fact that there is a need for local government institutions and their management to apply the provisions of the Atomic Law Act introduced in Poland in 2020. It is the implementation of Council Directive 2013/59/Euratom. The excessive requirements combined with highly repressive legal regulations imposed by the legislator on a wide range of various organizations located in the so-called “Radon Belt” may cause a strategic shock for these organizations in the near future. The void in literature that makes this study important are news blackouts, lack of both scientific and journalistic discussion, and the passivity of authorities in enforcing penalties for organizational units failing in their duties regarding measuring, informing, and reporting radiation levels, create a very dangerous scenario. It can be described as an administrative trap for many entities such as businesses, government offices, educational and cultural institutions, etc. The methodology in the study is literature review The most important findings in this paper is to raise awareness among the leadership of various organizational units about the threats arising from Directive 2013/59 Euratom, and further from the national legal acts. It also findings to stimulate scientific discussion in the field of quality management science regarding the important and dangerous phenomenon of introducing very restrictive legal regulations in an atmosphere of secrecy, or at least the absence of any information campaign.
Keywords: European Directive 2013/59/Euratom; Atomic law; strategic shock; administrative trap; radon duties